(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software Testing/System Testing is a critical element of assurance software quality that represents the main study of specifications, design, and coding. Increased visibility (capabilities) of the software as a system element and the "costs" that arise due to device failure lenient, motivates good planning through its testing thorough.Black-box testing techniques focus on the information domain of the software, by doing a test case by partitioning the input domain of a program in a way that provides in-depth testing coverage. The Black Box itself has several methods in testing. Namely, the test method Graph-based explores the relationship between objects and behavior program. The equivalent partition divides the input domain into data classes it is possible to perform certain software functions. Boundary value analysis check the program’s ability to handle data to the extent it can received.Evermos is a platform, a platform, to sell products Indonesian Muslims. As “Everyday Need for Every Moslem”, Evermos was started from a dream, vision and goal to helping small businesses and people individuals to compete with large and existing companies advanced. Testing software using the Black Box method is expected to increase visibility and meet quality requirements.Evermos software itself. The results of testing the software is aimed at finding errors in the category of functions incorrect, interface errors, errors in data structures or access external database, performance errors, initialization and termination errors.Evermos Web software test results is to provide documentation of test results which informs the suitability of the software being tested with predetermined specifications and finds errors on Evermos.